Forms of Work in Australia - Turner, Erin; Shomos, Anthony; Will, Lou (Productivity Commission, 2013)
The paper analyses changes in the prevalence of different forms of work in Australia over the decade to 2011, and explores possible explanations for observed changes.
Staff Working Paper
Productivity Commission
Keywords: Employment -- Hours; Employment -- Labour force participation; Labour market; Employment; Labour force participation; Hours; Employment and unemployment